METHODOLOGICAL APPROACH TO THE EVALUATION OF THE UKRZALIZNYTSIA BRAND EQUITY - Shcherbak, V. H. (Science and Transport Progress, 2008)
It is suggested a complex approach to estimation of value of the brand capital on the basis of application of various procedures in dependence of pursuit enterprise goals as well as a methodical approach to determination of correspondence of a given method to fixed goals of estimation for convenience of application of the given approach in practice is proposed. The effect of increase of brand capital can be reached not only due to the complex use of all elements of management system at an enterprise as a whole but also owing to use and development of separate unique properties of organisational potential of the enterprise.